2018
DOI: 10.1128/jvi.01674-18
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase/Akt and MEK/ERK Signaling Pathways Facilitate Sapovirus Trafficking and Late Endosomal Acidification for Viral Uncoating in LLC-PK Cells

Abstract: Sapoviruses cause acute gastroenteritis in both humans and animals. However, the host signaling pathway(s) that facilitates host cell entry by sapoviruses remains largely unknown. Here we demonstrate that porcine sapovirus (PSaV) activates both PI3K/Akt and MEK/ERK cascades at an early stage of infection. Removal of cell surface receptors decreased PSaV-induced early activation of both cascades. Moreover, blocking of PI3K/Akt and MEK/ERK cascades entrapped PSaV particles in early endosomes and prevented their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…The S1PR2 receptor is understudied in the intestine, but some evidence suggests that S1PR2 activation by BAs promotes proliferation (60,61). In LLC-PK1 cells, BAs directly activate signaling pathways (e.g., MEK/ERK cascades) required for PoSaV replication, although whether this requires a specific receptor remains unclear (62). Future studies will determine which signaling cascades are stimulated by BA-activation of S1PR2 in jejunal HIEs and if the activated signaling is required for HuNoV replication and possibly other caliciviruses in their individual model systems.…”
Section: And Ourmentioning
confidence: 99%
“…The S1PR2 receptor is understudied in the intestine, but some evidence suggests that S1PR2 activation by BAs promotes proliferation (60,61). In LLC-PK1 cells, BAs directly activate signaling pathways (e.g., MEK/ERK cascades) required for PoSaV replication, although whether this requires a specific receptor remains unclear (62). Future studies will determine which signaling cascades are stimulated by BA-activation of S1PR2 in jejunal HIEs and if the activated signaling is required for HuNoV replication and possibly other caliciviruses in their individual model systems.…”
Section: And Ourmentioning
confidence: 99%
“…However, a recent study suggested that sapovirus, another non-enveloped virus, activates PI3K-AKT signaling cascade via the PSaV-binding to the cell surface carbohydrate receptors. 31 It is possible that EMCV activates NF-κB with similar mechanisms. TGR5, which is a GPCR receptor for BAs, is located at both the plasma and intracellular organelle membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The direct binding of PKA or AMPK to any of the V-ATPase subunits has not been demonstrated. However, it has been shown that activated pPI3K, pAKT and pERK associate with the E subunit during virus replication [123][124][125]. A quick search through the PhosphoSitePlus database (phosphosite.org), a curated site for phosphorylation and ubiquitylation sites identified by high throughput mass spec analysis, revealed that all of the V-ATPase subunits are modified.…”
Section: V-atpase As a Signalsomementioning
confidence: 99%